Eurosclerosis or Financial Collapse : Why Did Swedish Incomes Fall Behind? - Cerra, Valerie (IMF Working Papers; Working Paper ;, 2005)
Sweden represents an archetypal welfare state economy, with extensive government safety nets. Some scholars have attributed a decline in its per capita income ranking since 1970 to "eurosclerosis" or sluggish growth caused by distortionary policies. This paper argues rather, that the permanent loss in output following Sweden's banking crisis in the early 1990s explains the decline in its per capita GDP ratings. The paper finds no macroeconomic evidence that welfare state policies have deterred growth. The results warn that empirical growth analyses should distinguish between trend output growth and permanent output loss associated, for example, with financial crises.